(untitled) (Revista Brasileira Multidisciplinar, 2008)
Modern civilization, in recent years, has increased the requirement of products derived from iron and steel, stimulating the growth of the national siderurgical sector and, consequently, the generation of industrial residue called basic slag. In this context, the recycling of residues can contribute to solve problems of the industries that give priority to the excellence of the production with quality. On the other hand, there is a sector of primary production in Brazil, the agriculture, with a great cultivated area in acid ground and with low fertility, being these factors admittedly determinative for vegetal production, under tropical conditions. Thus, there is a scenery of two primary sectors of production, although distinct ones, that present interaction potential, for , on one hand, there is disponibility of a product with similar properties to the liming materials and traditional fertilizers and, on the other hand, a production sector that is highly dependent of these products. And the interaction between these two sectors helps in the preservation of the environment, bringing, thus, a certain sustainability in the production systems of the postmodern civilization that will be the challenge of this new century. Considering the current possibility of recycling these industrial residues in agriculture, three important factors have to be taken into account. The first would be the proper use of the abundant, available and promising industrial residue; the second, in a propitious agricultural environment, acid soil and low fertility; and third, in a responsive and important socio-economic culture, the sugar cane, considering its vast cultivated area. In national literature, few works have dealt with the use of the basic slag and have evaluated the reply of the cultures to its application. Thus, the present work had as its aim to gather information from literature concerning the characterization and production of basic slag in Brazil, as well as the agronomic viability of its use in sugar cane, pointing benefits in the liming of the soil and in the supply of nutrients and silicon.